2003
DOI: 10.1080/02844310310019464
|View full text |Cite
|
Sign up to set email alerts
|

Functional nerve recovery after bridging a 15 mm gap in rat sciatic nerve with a biodegradable nerve guide

Abstract: Recovery of nerve function was evaluated after bridging a 15 mm sciatic nerve gap in 51 rats with a biodegradable poly(DL-lactide-epsilon-caprolactone) nerve guide. Recovery of function was investigated by analysing the footprints, by analysing video recordings of gait, by electrically eliciting the withdrawal reflex, by nerve conduction velocity and by electromyography (EMG). Sensory nerve function recovered as measured by electrostimulation. Motor nerve function partly recovered but electromyograms remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…On the other hand, recordings from the gastrocnemius muscle have been applied in various studies. These studies do not contain any inconsistencies about recording from gastrocnemius muscle [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recordings from the gastrocnemius muscle have been applied in various studies. These studies do not contain any inconsistencies about recording from gastrocnemius muscle [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…15 This suggests that the factors which guided the outgrowing motor axons towards their target muscles at initial stages of development (e.g. reorganizations of neural circuits at spinal levels or compensations or 'relearning' at central levels) are no longer effective at this age in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In another peripheral vascular study performed in 1994, it was concluded that muscle atrophy of the injured limb was responsible for the reduction of the stance duration. 56 The relation of stance phase duration at the operated and nonoperated sides, de®ned by the stance factor, was considered by Dijkstra et al 62 and Meek et al 68 to be a precise method for the evaluation of functional motor nerve recovery in a nerve guide model. Recently, in sciatic and tibial nerve injury models, the shortened stance phase was related to a decreased power in the injured limb.…”
Section: 64à66mentioning
confidence: 99%